Effect Factors Of Psychophysical And Biomechanical Of Upper Quadrant Musculoskeletal Disorder Among Young Drivers - Ahmad, Intan Fatihah (2016)
Musculoskeletal disorder is commonly associated with driver fatigue problem.Previously, various techniques were proposed to the influence of changes in physical and psychosocial conditions on musculoskeletal disorders. However, the impact factors contribute to the musculoskeletal disorder is still more to achieve. This research aims to identify impact of psychophysical experience, biomechanical and heart rate of drivers towards prevalence musculoskeletal disorder. Moreover, the relationship between presence of musculoskeletal disorder with Time, Gender, BMI and Length of Arm (LoA)will be evaluated.Participant will be asked to driving for 30 minutes and repeat the procedure for two times. At the same time, the movement of the participant while driving will be capture by Motion Capture and video also is taken.Meantime, the Heart rate of the participant while driving is monitor. Between the replication, the participant will be given questionnaire sheet to be answered. The questionnaire sheet will be answered the part of the participant’s body feeling discomfort during the experiment where this discomfort part is potential for musculoskeletal disorder prevalence. Results identified both upper arm and lower arm problem. Biomechanical analyses found static posture of arm and undesirable wrist positions lead to discomfort.Although the results were promising, there were still some limitations that need to be overcome in future study.